The Role of PAI Teachers' Social Competence in the Learning Process - B.S, Iman Asroa; Mastura, Lidiya Fadhlah (International Journal of Humanities, Education, and Social Sciences, 2023)
This study examines the role of social competence possessed by PAI teachers on the PAI learning process at SMP IT Insan Kamil Batusangkar. The background of this research is the influence caused as a result of the social competence of PAI teachers at SMP IT Insan Kamil Batusangkar. Based on these problems, a research question arises in the form of what is the role of the social competence of PAI teachers in the PAI learning process at SMP IT Insan Kamil Batusangkar? The research was conducted with a qualitative approach using field research methods. Data were collected by conducting field observations and interviews with PAI teachers and teacher and student councils. The data obtained were processed using the Miles & Huberman data analysis method by collecting data, reducing the data that had been collected, analyzing and presenting the results of data analysis. From the results of the analysis, it is concluded that the social competence of PAI teachers plays a very important role in the PAI learning process at SMP IT Insan Kamil Batusangkar. This role can be seen in the ongoing learning process, student achievement, and student social intelligence.